Persistence and Nonpersistence of a Predator Prey System with Stochastic Perturbation - Haihong Li; Daqing Jiang; Fuzhong Cong; Haixia Li (Abstract and Applied Analysis)
We analyze a predator prey model with stochastic perturbation. First, we show that this system has a unique positive solution. Then, we deduce conditions that the system is persistent in time average. Furthermore, we show the conditions that there is a stationary distribution of the system which implies that the system is permanent. After that, conditions for the system going extinct in probability are established. At last, numerical simulations are carried out to support our results.